Study on the mechanism of cobalt recovery from waste lithium cobaltate batteries in citric acid system - X. Y. Liu; Y. Y. Wang; H. Jin (Metalurgija, 2024)
The waste lithium cobalt acid batteries were utilized as raw materials to separate out LiCoO2 cathode material. Citric acid was used to leach cathode material, and LiCoO2 leaching solution was electrodeposited to obtain cobalt plating, in the meantime the Li2+ ions were enriched. The optimized conditions of leaching process are 1,2 mol/L citric concentration and 0,35 mol/L sodium thiosulfate concertation, the leaching efficiency of cobalt and lithium is 97,5 % and 97,0 % respectively. At pH 4, the smooth cobalt coating with fine grains can be obtained on the surface of the stainless-steel cathode.